2017
DOI: 10.3329/cardio.v9i2.32417
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Left Main Coronary Artery Occlusion by ST Segment Elevation in Lead aVR Greater than that in Lead V1 in Acute Coronary Syndrome

Abstract: Background: The electrocardiogram (ECG) predicting an acute obstruction of the LMCA, which requires immediate aggressive treatment, is very important for early diagnosis. We correlated ST segment elevation in lead aVR greater than that in lead V• with coronary angiographic diagnosis of LMCA occlusion in patients with acute coronary syndrome.Methods: Cross sectional analytical study was conducted in the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh from Augus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Additionally, it was found that prolonged QRS duration was related to poor prognosis in anterior AMI. [5][6][7][8] Another study showed that patients with prolongation of QRS duration had increased ventricular volume, decreased left ventricular EF, and higher incidence of sudden cardiac death. 9 ECG can be used as a cheap, easily available and reproducible test for early stratification of patients with acute anterior MI.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was found that prolonged QRS duration was related to poor prognosis in anterior AMI. [5][6][7][8] Another study showed that patients with prolongation of QRS duration had increased ventricular volume, decreased left ventricular EF, and higher incidence of sudden cardiac death. 9 ECG can be used as a cheap, easily available and reproducible test for early stratification of patients with acute anterior MI.…”
Section: Introductionmentioning
confidence: 99%